2005
DOI: 10.1080/10715760500166693
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide and hydrogen peroxide formation during enzymatic oxidation of DOPA by phenoloxidase

Abstract: Generation of superoxide anion and hydrogen peroxide during enzymatic oxidation of 3-(3,4-dihydroxyphenyl)-DL-alanine (DOPA) has been studied. The ability of DOPA to react with O2*- has been revealed. EPR spectrum of DOPA-semiquinone formed upon oxidation of DOPA by O2*- was observed using spin stabilization technique of ortho-semiquinones by Zn2+ ions. Simultaneously, the oxidation of DOPA by O2*- was found to produce hydrogen peroxide (H2O2). The analysis of H2O2 formation upon oxidation of DOPA by O2*- usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The source of ROS is multiple and includes various physiological procedures or organelles, such as biosynthesis of melanin (Slominski et al, 2004), altered tumor metabolism, and immune reactions (Komarov et al, 2005;Wittgen and van Kempen, 2007). Our observation that Nox1 is ubiquitously overexpressed in all melanoma cell lines suggests that Nox1 overexpression may contribute to the observed high ROS levels in melanoma cells.…”
Section: Discussionmentioning
confidence: 87%
“…The source of ROS is multiple and includes various physiological procedures or organelles, such as biosynthesis of melanin (Slominski et al, 2004), altered tumor metabolism, and immune reactions (Komarov et al, 2005;Wittgen and van Kempen, 2007). Our observation that Nox1 is ubiquitously overexpressed in all melanoma cell lines suggests that Nox1 overexpression may contribute to the observed high ROS levels in melanoma cells.…”
Section: Discussionmentioning
confidence: 87%
“…In view of the toxicity of prophenoloxidase products such as quinones (Pardini, 1995) and radicals (Kamarov et al, 2005) and the ability of apolipophorin-III of M. disstria to activate prophenoloxidase (al beit to a limited extent), the apolipoprotein may not exist in the free form unattached to other molecules to ensure insect survival. In G. mellonella, apolipophorin-III is associated with apolipophorin-II (Halwani et al, 2000) and in other species, with lipophorin particles or other recognition receptors which collectively form a cage around foreign molecules limiting antigen damage (Rahman et al, 2006;Ma et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…[18] It thus appears that the mechanism of catechol oxidation by the model compounds is very intricate, which evidently explains often contradictory literature reports on the catalytic behavior of copper(II) complexes. It is also very interesting to note that some authors have recently reported the formation of dihydrogen peroxide, [44] as well as semiquinone radicals, [45] during the catalytic oxidation of DOPA by the structurally related enzyme tyrosinase in haemolymph of some insects. Although neither of these species has to the best of our knowledge ever been observed during the substrate oxidation by catechol oxidase, the question about the possibility of two different catechol oxidation pathways for the natural enzyme, as found for model compounds, still needs to be answered.…”
Section: Discussionmentioning
confidence: 99%